The curriculum as a tool for inclusive participation: Students' voices in a case study in a Portuguese multicultural school - César, Margarida (2012)
Portuguese schools in urban areas became multicultural during the 90s. Some students are quite distanced from the school culture. Many repeat grades. The curriculum emerges as a means of (re)organizing school practice, so that it is designed to foster inclusion. It is a tool for social mediation between the culture and knowledge of teenagers, and academic ones. It shapes the interactions between participants, cultural tools and knowledge. The principles of inclusive schooling promote the respect for diversity, underlining the need to listen to all voices of a learning community. According to the socio-cultural approach appropriating knowledge and developing competencies is a complex process. Interactive practices shape students’ academic performances. Collaborative project work has been used to promote students’ engagement. This action-research project developed an alternative curriculum in a class (grades 5 and 6) from a poor and multicultural school in Lisbon. A follow-up investigated the impact of the educational changes on the learners’ participation in school and in social practices, and on their future life. We aim at analyzing this alternative curriculum process by focussing on students’ narratives. Results highlight improvements in students’ academic and social competencies. Changing practices during compulsory education facilitated achievement and resulted in a better socialization.